Information and communications technology (ICT) and teaching-learning capacity: the classroom management interconnectivity - Akinlove, Gbadegesin; Adu, Emmanuel Olusola; Adu, Kemi Olajumoke; Olawumi, Kayode Babatunde (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper is a desktop study that adopts a theoretical approach of the classroom management interconnectivity between information and communications technology and Social Studies in the Educational Institutions of both secondary and tertiary institutions. The paper discusses classroom management interconnectivity between information and communications technology and social studies. ICT is understood as a complex of artifacts, techniques, and knowledge for solving human problems involving information and its communication. One major feature is the employment of electronics rather than mechanical means for storing, processing, and communicating social studies information. It is noted that when communication is hampered in the administration of any organization, the entire organization suffers, when it is accurate, thorough, and timely, the organization can move so effectively and efficiently towards goal achievement. The paper, therefore, examines the specific objectives of ICT, the major terminologies, the relevance of ICT, challenges, and way-outs of the challenges. It is therefore recommended that Social studies education must engage in constant self-development in information and communications technology, orientation courses, and symposium, conferences, debates, seminars should be encouraged and emphasis should be laid on the teaching of values of ICT. Finally, it is recommended that federal and state governments should ensure a sustainable supply of electricity to all institutions of learning in both rural and urban areas.